RFID based smart hospital management system: A conceptual framework - Mahmood, Nadeem; Shah, Asadullah; Waqas, Ahmad; Bhatti, Zeeshan; Abubakar, Adamu; M. Malik, H. Abid (Institute of Electrical and Electronics Engineers, Inc., 2014)
The integration of information and communication technology (ICT) in the healthcare sector has been one of the important areas of research since last two decades. The application of RFID (Radio Frequency Identification) technology is widely used in healthcare sector to provide better, reliable and secure services. RFID systems are integrated into hospital information systems and provide full automation and streamline the important modules of patient identification, staff allocation, doctors, medicines and treatments. In this paper, we propose RFID based conceptual framework for smart hospital management system which provides a safe and secure patient data management system. We also highlight the importance of RFID in healthcare domain with the help of an example case study with a working prototype application.